The specialized reproductive mode of the treefrog Aplastodiscus perviridis (Anura : Hylidae) - Haddad, CFB; Faivovich, J.; Garcia, PCA (Brill Academic Publishers, 2005)
Males of the South American treefrog Aplastodiscus perviridis construct concealed subterranean nests. Using a complex courtship behavior that involves tactile stimuli and vocalizations, males guide the females to the subterranean nests where eggs are laid. Embryos and facultatively oophagous tadpoles (at least in stage 25) stay in subterranean nests until flooding transports them to ponds or streams. This is a rare reproductive mode previously known for few species in the Hyla albosignata and H. albofrenata complexes. Based on similarities of reproductive mode we suggest a monophyletic origin for Aplastodiscus and these complexes of Hyla.